Answer :

2x2 - x - 6 = 0


Using the splitting middle term - the middle term of the general equation is divided in two such values that:


Product = a.c


For the given equation a = 2 b = - 1 c = - 6


= 2. - 6 = - 12


And either of their sum or difference = b


= - 1


Thus the two terms are - 4 and 3


Difference = - 4 + 3 = - 1


Product = - 4.3 = - 12


2x2 - 4x + 3x - 6 = 0


2x(x - 2) + 3(x - 2) = 0


(x - 2) (2x + 3) = 0


x = 2 x = - 3/2

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses